Application of Cosmology Concepts to Nias Cultural Park Planning (International Journal of Architecture and Urbanism, 2022)
Nias tribe has a variety of cultures that are the heritage of their ancestors. One of them is the belief in cosmologists, namely that the world is divided into the underworld and the upper world. This cosmological conception was applied to the design of cultural parks in Nias. The goal is to create a cultural park architecture that can reflect the art and culture of Nias itself. Cosmological concepts in this design are applied from selecting building sites that are a more macro thing to the organization of space, forming the mass of buildings, to building materials that are more micro things. The data collection method used is a qualitative descriptive method. This cultural park will be one of the cultural preservation containers that can characterize the richness of Nias culture from the image of its architecture.